Alterations in histological structure, blood estrogen and progesterone levels after oral administration of garlic extract in yellowfin seabream (Acanthopagrus latus) - Solmaz Kakeshian; Solmaz Shirali; Ahmad Savari; Hossein Najafzadehvarzi; Mohammad Zakeri (تغذیه آبزیان, 2022)
In this study, the effects of garlic phytoestrogen extract on gonad maturation along with estrogen and progesterone levels in yellowfin seabream (Acanthopagrus latus) were investigated. A total of 60 yellowfin seabreams were caught from Naseri pond in Khuzestan Province, Southwest Iran and transported to the laboratory. Fish were treated in four groups receiving garlic extract with doses of 0 (control), 0.5, 1 and 2 % of diet (T1, T2 and T3, respectively). Each treatment consisted of three replicates. The fish were fed twice a day at 3% of body weight for 14 days. For histological study, samples were taken from the gonads. In order to assay the hormone levels, samples were taken from the caudal vein of the fish on days 0, 7, 10 and 14. The histological results showed that garlic extract in the lowest dose caused a decrease in vitellogenesis, however, in higher doses an elevation in vitellogenesis and also the tendency of this hermaphrodite fish gonads to be female. The highest amount of vitellogenesis was reported in T1 on 10th day. In total, elevating in the amount of this extract initially upraised the number of vitellogenic follicles and promotion of ovarian maturation. However, higher doses and also increasing the administration time of the extract exhibited inverse results. Measuring the levels of hormones showed a significant change in their plasma levels during the experiment, so that an increase in level of estrogen was observed in all three prescribed doses and an increase in level of progesterone was observed in higher doses (T2 and T3; p<0.05). The results of the present study indicate the effect of garlic phytoestrogen extract on growth and maturation of ovaries.